Treatment of postpill amenorrhea with abdominal obesity by traditional Korean medicine treatment focused on pharmacopuncture and moxibustion: A case report. Issue 35 (August 2019) - Hwang, Ji Hye
Abstract: Rationale: Hormone imbalance and menstrual irregularities are normal for postpill women. Pharmacopuncture and moxibustion can stimulate acupoints with herbal extract and heat, respectively, to regulate the function of qi and blood, expel pathogens, and support health. Patient concerns: A 39-year-old female patient presented with amenorrhea, >6 months after she had stopped taking the oral contraceptive pill, which she had taken for more than 10 years, and possible associated infertility. Additionally, she reported sudden weight gain of approximately 12 kg in 1 year. Diagnoses: In this study, we examined the amenorrhea lasted more than 6 months for postpill patient. Interventions: She refused a strong acupuncture stimulus; she underwent lower abdomen pharmacopuncture with wild ginseng complex (WGC) and moxibustion at CV4, 5 times during 1 month. As a secondary treatment, 1 g Geoseub-hwan pills were prescribed for overeating and during social events. After 5 weekly primary treatments, Geoseub-hwan was prescribed intermittently. Outcome: After 3 primary treatments, she began menstruation without menstrual cramps or discomfort. After 5 treatments, she exhibited improvement of body weight and body composition. At 1- and 3-month follow-up examinations, she confirmed regular menstruation without discomfort. Lessons: Pharmacopuncture with WGC and moxibustion may be effective for the treatment of postpill amenorrhea with abdominal obesity and can be used for patients with fear of a strong acupuncture stimulus.